Effect of advanced chelate compounds-based mineral supplement in laying hen diet on the performance, egg quality, yolk mineral content, fatty acid composition, and oxidative status. (1st January 2022) - Ghasemi, Hossein Ali; Hajkhodadadi, Iman; Hafizi, Maryam; Fakharzadeh, Saideh; Abbasi, Meysam; Kalanaky, Somayeh; Nazaran, Mohammad Hassan
Highlights: Advanced chelate compound-based trace minerals (OTM) were evaluated in laying hens. Replacement of inorganic minerals with 33% OTM supported laying performance. 66% and 100% OTM supplementation increased Se and Zn concentrations in yolk. 66% and 100% OTM supplementation improved lipid profiles and oxidative status. Abstract: The study aimed to determine the efficiency of advanced chelate compounds-based trace minerals (OTM) in laying hens. Laying hens (240, 32 weeks old) were assigned to one of the following five groups: NOTM (no added trace minerals), CONTM (standard mineral salts), and three experimental groups in which chelates were used to replace 33, 66, and 100% of mineral salts (OTM33, OTM66, and OTM100, respectively). Each treatment had six replicates with eight hens per replicate. After 18 weeks, performance and physicochemical properties of eggs in all experimental groups was better than those in the NOTM group. Among the treatments, OTM66 and OTM100 produced the best results in terms of laying performance, yolk PUFA/SFA ratio, Zn and Se contents, and malondialdehyde concentration in both serum and yolk. In conclusion, up to 66% OTM supplementation was beneficial for performance, lipid and mineral composition of yolk, and oxidative status.